Alternative approach to measure the Brazilian municipal development: the Relative Municipal Development Index - Gonçalves Mendes Barbosa, Francis Régis; Schlindwein, Madalena Maria; Corrêa da Silva, Marcelo (Economía Sociedad y Territorio, 2024)
Amartya Sen's theory of Development as Freedom states the prediction of development by evaluating the expansion of individual freedoms. This study operationalizes this theory and its instrumental freedoms through the construction of a development index and multivariate statistics. Spatiality of municipal development provides empirical evidence for interrelations between instrumental freedoms defended by this theory. The determinants of development related mainly to income and its distribution, but also housing conditions and social vulnerabilities. The findings unmask the geographic structure of (under) development in a frontier in Mid-West Brazil, marked by higher deprivation of opportunities, precarious services and greater economic stagnation.